Special paperSudden cardiac arrest in takotsubo cardiomyopathy – a case study - Sosnowska-Pasiarska, Barbara; Bąkowski, Dawid; Woronowicz-Chróściel, Agnieszka; Wożakowska-Kapłon, Beata (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
We present a 59-year-old woman who was admitted to hospital after sudden cardiac arrest due to ventricular fibrillation. Finally takotsubo syndrome was diagnosed. In the acute phase of takotsubo syndrome life-threatening ventricular arrhythmias and significant hemodynamic disorders may occur due to strong adrenergic stimulation and myocardial ischemia. It has been proved that the occurrence of torsade de pointes tachycardia in the acute phase of takotsubo cardiomyopathy is associated with QT prolongation. There are no clear guidelines on pharmacological treatment and implantable cardioverter defibrillator implantation after a past takotsubo episode. Takotsubo cardiomyopathy has not been entirely explained as an etiological disease.